Quel rôle l’utilisation du téléphone portable joue-t-il dans la construction des compétences de mobilité au Cameroun ? - Jérémy Pasini (Netcom)
This article proposes an understanding of how the use of mobile phones contributes to the accumulation and implementation of mobility skills in Cameroon. Being mobile is an essential prerequisite in an urbanizing country where jobs, services and family members are increasingly spread throughout space. The main aim of this contribution is therefore to report on the efforts and strategies deployed by individuals to integrate into the "dispersed society". The results indicate that the use of mobile phones facilitates the practical implementation of mobility (orientation, overcoming travel difficulties, etc.), but also represents a new source of risk (theft) to which users try to provide answers.